Cover Feature: Asymmetric Organocatalysis Accelerated via Self‐Assembled Minimal Structures (Eur. J. Org. Chem. 39/2021). Issue 39 (4th October 2021) - Sinibaldi, Arianna; Della Penna, Francesca; Ponzetti, Marco; Fini, Francesco; Marchesan, Silvia; Baschieri, Andrea; Pesciaioli, Fabio; Carlone, Armando
Abstract : The Cover Feature shows the catalytic activity exerted by a minimalistic peptide behaving as an organocatalyst in a Michael addition. A supramolecular arrangement on the catalyst in fibrils showed to remarkably improve the TOF of the catalyst. The aldehyde donors and nitroalkenes acceptors are represented in the top left corner and are largely converted to the adduct as the reaction proceeds, towards the bottom right. Across the image the self‐assembled fibrils of a minimalistic tripeptide, catalyzing the reaction, are shown; the tripeptide is shown in detail, colored green, for one of the fibrils. Image credit: Nicola De Mitri. More information can be found in the Communication by A. Carlone et al .